Exploring perspectives on the approach for teaching ablaut principles to English L2 learners: a case study in South African secondary schools - Farisani Thomas Nephawe; Matodzi Nancy Lambani (Journal on English as a Foreign Language, 2023)
Although regular and irregular verb morphological processes in the simple past are invaluable approaches for enhancing communication, the formation of irregular verbs, including the ablaut principles, suppletion principles, and backformation, for example, pose challenges to the majority of English second language (L2) learners. Also, most teachers experience difficulties in teaching ablaut principles to their learners. The irregular verb morphological processes in the simple past tense are a challenge to many. The present study aimed to explore teachersâ€™ perspectives on the approach for teaching ablaut principles to L2 learners. A qualitative research approach with a case study design was espoused because it provides an in-depth understanding of a particular phenomenon. Four purposively sampled teachers were interviewed and observed when teaching Grade 8 English L2 learners at Dzindi Circuit, South Africa. A Delve Thematic Analysis Software Version 22.0 was utilised because it uses and codes, identifies, and summarises perceptionsÂ within interview transcripts. Preliminary investigation indicated that learners were incompetent in using the ablaut principles. After employing game-based teaching approaches, learners performed outstandingly. The study acclaims using the identified approaches in the teaching and learning of the ablaut principle in the simple past tense, and further research is encouraged on the current topic.